The Effect Of Green Organizational Culture And Green Reward On Organizational Citizenship Behavior With Organizational Commitment As Intervening Variables - Norma Sari Putri, Audi; Mustafa E. Q, Zainal (Green Publisher Indonesia, 2022)
Green Human Resources Management (GHRM), known as